Methods for certification in colonoscopy – a systematic review. (4th March 2018) - Preisler, Louise; Svendsen, Morten Bo Søndergaard; Svendsen, Lars Bo; Konge, Lars
Abstract: Introduction: Reliable, valid, and feasible assessment tools are essential to ensure competence in colonoscopy. This study aims to provide an overview of the existing assessment methods and the validity evidence that supports them. Methods: A systematic search was conducted in October 2016. Pubmed, EMBASE, and PsycINFO were searched for studies evaluating assessment methods to ensure competency in colonoscopy. Outcome variables were described and evidence of validity was explored using a contemporary framework. Results: Twenty-five observational studies were included in the systematic review. Most studies were based on small sample sizes. The studies were categorized after outcome measures into five groups: Clinical process related outcome metrics ( n = 2), direct observational colonoscopy assessment ( n = 8), simulator based metrics ( n = 11), automatic computerized metrics ( n = 2), and self-assessment ( n = 1). Validity score varied among the studies and only five studies presented sufficient evidence to recommend the tool for clinical assessment. Conclusions: The objectives vary throughout the presented tools. Some tools are global tools where others focus on procedural technical skill assessment or even part-task skills. There is a tendency in the most recent studies towards more specific assessment of technical skills. The majority of assessment methods lack sufficient validity evidence.